Implementation of International Humanitarian Law in Nepal - Tiwari, Laxman (JMC Research Journal, 2025)
This study critically examines Nepal’s adherence to International Humanitarian Law (IHL) by tracing its historical evolution, assessing current enforcement mechanisms, and identifying gaps. The global imperative for accountability post-World War II needs rigorous compliance with IHL conventions. This study’s objective is to evaluate Nepal’s legislative and practical adherence to these conventions. The central problem identified is Nepal’s absence of specific laws to repress IHL violations, despite positive judicial attitudes and training initiatives for military personnel. Methodologically, the study employs a comprehensive review of legal texts, judicial decisions, and policy documents, supplemented by interviews with legal experts and practitioners. The findings reveal a significant compliance failure, highlighting the urgent need for robust national legislation to combat impunity, ensure victim reparations, and prosecute offenders both domestically and internationally if necessary. The conclusion underscores that effective IHL implementation is crucial for upholding international legal standards and ensuring justice for victims of war crimes.